Prolactin Hormone Profile, Patterns and Expression Level of Prolactin, Pit-1, VIP and PREB Gene in Kampung Chicken (Gallus gallus domesticus) Induced by Anti-Prolactin - Bana , Joice J.; Barlian, Anggraini; Ridwan, Ahmad (International Journal of Poultry Science, 2021)
Background and Objective: Prolactin is a steroid hormone that induces broodiness in chickens. In addition to the prolactin hormone, the incubating nature of chickens is also influenced by genes. The purpose of this study was to analyze changes in the profile of the prolactin hormone; the pattern and level of expression of the genes Prolactin (Prl), Vasoactive Intestine Peptide (VIP), Pituary specific transcription factor-1 (Pit-1) and prolactin regulatory element binding protein (PREB) due to the administration of each dose of antiprolactin (2-Bromo-α-Ergocryptine Methanesulfonate salt/Bromocriptine); as well as the relationship between prolactin hormone secretion and these genes. Materials and Methods: Blood and brain samples from 25 hens (Kampung chickens) fed various doses of anti-prolactin were used in this study. Serum from each blood sample was used to calculate the concentration of the hormone prolactin by ELISA method. Meanwhile, the brains of each free-range chicken were used to measure the pattern and level of expression of the Prl, VIP, Pit-1 and PREB genes using the Quantitative Real Time-Polymerase Chain Reaction (RT-qPCR) method. Results: Increase in the doses of anti-prolactin decreased the concentration of the hormone prolactin as well as the pattern and level of expression of the Prl, VIP, Pit-1 and PREB genes. Conclusion: Anti-prolactin can inhibit the secretion of the hormone prolactin and the expression of Prl, Pit-1, VIP and PREB genes.